TheraCal LC: From Biochemical and Bioactive Properties to Clinical Applications. (26th March 2018) - Arandi, Naji Ziad; Rabi, Tarek
Abstract : Background . Direct pulp capping is a popular treatment modality among dentists. TheraCal LC is a calcium silicate-based material that is designed as a direct/indirect pulp capping material. The material might be very attractive for clinicians because of its ease of handling. Unlike other calcium silicate-based materials, TheraCal LC is resin-based and does not require any conditioning of the dentine surface. The material can be bonded with different types of adhesives directly after application. There has been considerable research performed on this material since its launching; however, there are no review articles that collates information and data obtained from these studies. This review discusses the various characteristics of the material with the aim of establishing a better understanding for its clinical use. Methods . A search was conducted using search engines (PubMed and Cochrane databases) in addition to reference mining of the articles that was used to locate other papers. The process of searching for the relevant studies was performed using the keywords pulp protection, pulp capping, TheraCal, and calcium silicates. Only articles in English published in peer-reviewed journals were included in the review. Conclusion . This review underlines the fact that further in vitro and in vivo studies are required before TheraCal LC can be used as a direct pulp capping material.